Cultural Influences on Teluk Awur Community Perceptions of Education - Fadilah, Yuniardi; Pramudya, Akmal Dwi (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS)
Jepara regency, statistically speaking, is one of area with a low poverty rate. This is considered to be due to the lack of opportunities for education. However, it is often argued the other way around, that the difficulty of education is due to poverty. As one of the regions in Jepara, Teluk Awur also shows a tendency to make this argument in relation to education and poverty. Therefore, this study seeks to examine the perceptions of the people of Teluk Awur on the importance of education. As a qualitative study, the research will attempt to describe the perceptions of the people of Teluk Awur and look at the factors that influence these perceptions. In this case, the research will try to see the interaction between culture and society in building the perception of the importance of education for the people of Teluk Awur.